Construction and evaluation of in house pcrbased diagnostic method for detection of helicobacter pylori infection - Siti Suraiya, Md Noor (Pusat Pengajian Sains Perubatan, 2013)
The specific primers for He/icobacter pylori were constructed. The primer were standardized and optimized by using ATCC strains. The PCR were performed to eighty-nine antral biopsy samples from patients suspected to have gastric ulcer. Simultaneously, histopathological examination was performed on the biopsy samples. The agreement between the two test methods was measured.